How Integrated Marketing Communications (IMC) works? A theoretical review and an analysis of its main drivers and effects (Communication & Society, 2012)
Since the mid-1990’s, the concept of Integrated Marketing Communications (IMC) has come to the fore and attracted considerable attention in the literature. The main purpose of this paper is twofold: (1) to explore IMC by delimitating its conceptual boundaries and identifying its main dimensions and (2) to develop a whole theoretical model of its antecedents and consequences. To achieve this goal, this study analyzes the conceptual framework around IMC and its dimensions and it presents an extensive literature review. Moreover, a new definition is presented and the main dimensions of the concept are highlighted. A systematic literature review is carried out to identify IMC antecedents and consequences and the research hypotheses are formulated. Following the obtained results, a conceptual model has been developed and the most relevant findings are discussed. Finally, the main academic and managerial implications are described. This model will help academics and marketers to better understand the role that this new marketing paradigm plays within modern management, in identifying the key variables that promote or hinder IMC and the benefits derived from its implementation.